2020
DOI: 10.1111/ina.12680
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of far‐field human cough airflows from healthy and influenza‐infected subjects

Abstract: Seasonal influenza epidemics have been responsible for causing increased economic expenditures and many deaths worldwide. Evidence exists to support the claim that the virus can be spread through the air, but the relative significance of airborne transmission has not been well defined. Particle image velocimetry (PIV) and hot‐wire anemometry (HWA) measurements were conducted at 1 m away from the mouth of human subjects to develop a model for cough flow behavior at greater distances from the mouth than were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
3
31
1
Order By: Relevance
“…The initial velocity at t = 0 s is ∼4.0 m/s and then rapidly increases to 15.0 m/s at t = 0.03 s. The velocity gradually reduces to 4.0 m/s at time t = 0.08 s. The variation in the velocity qualitatively agrees with the results given by Gupta et al (2009) , Dudalski et al (2020) , and Kwon et al (2012) . However, Dudalski et al (2020) reported that the peak velocity value is ∼22.0 m/s at t = 0.068 s, which is different from the present result. A potential reason for the difference is that the position of the mouth and the onset time of coughing are slightly different among the volunteers in our experiments.…”
Section: Resultssupporting
confidence: 86%
“…The initial velocity at t = 0 s is ∼4.0 m/s and then rapidly increases to 15.0 m/s at t = 0.03 s. The velocity gradually reduces to 4.0 m/s at time t = 0.08 s. The variation in the velocity qualitatively agrees with the results given by Gupta et al (2009) , Dudalski et al (2020) , and Kwon et al (2012) . However, Dudalski et al (2020) reported that the peak velocity value is ∼22.0 m/s at t = 0.068 s, which is different from the present result. A potential reason for the difference is that the position of the mouth and the onset time of coughing are slightly different among the volunteers in our experiments.…”
Section: Resultssupporting
confidence: 86%
“…With active breathing, sneezing and coughing, small droplets are formed, which consist of water, air, tiny particles (d p < 10 –6 m) and respiratory fluid. These components of human reflex processes have different rates and duration (time) of generation and, accordingly, lead to different effects on the environment and the human body 11 13 . The distance that these droplets can travel directly depends on the size of the droplets themselves and the speed of its propagation 14 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 35 ] measured the airflow velocity and droplets involved in exhaled cigarette smoke of coughs using PIV and reported the statistical relationship between velocity magnitude with time or coordinate. Dudalski et al [ 36 ] measured the far-field human cough airflows from healthy and influenza-infected subjects, and obtained the time variation of peak velocity in the center of airflow jet but did not discuss the velocity distributions. Wang et al [ 37 ] measured the velocity using PIV and captured droplets on a solid surface that subjects faced when coughing.…”
Section: Introductionmentioning
confidence: 99%